Evaluation of NGS and RT-PCR Methods for ALK rearrangement in European NSCLC patients: results from the European Thoracic Oncology Platform Lungscape project - Letovanec, Igor; Warth, Arne; Dienemann, Hendrik (Journal of thoracic oncology, 2018)
Introduction: The reported prevalence of ALK receptor tyrosine kinase gene (ALK) rearrangement in NSCLC ranges from 2% to 7%. The primary standard diagnostic method is fluorescence in situ hybridization (FISH). Recently, immunohistochemistry (IHC) has also proved to be a reproducible and sensitive technique. Reverse-transcriptase polymerase chain reaction (RT-PCR) has also been advocated, and most recently, the advent of targeted next-generation sequencing (NGS) for ALK and other fusions has become possible. This study compares anaplastic lymphoma kinase (ALK) evaluation with all four techniques in resected NSCLC from the large European Thoracic Oncology Platform Lungscape cohort. Methods: A total of 96 cases from the European Thoracic Oncology Platform Lungscape iBiobank, with any ALK immunoreactivity were examined by FISH, central RT-PCR, and NGS. An H-score higher than 120 defines IHC positivity. RNA was extracted from the same formalin-fixed, paraffin-embedded tissues. For RT-PCR, primers covered the most frequent ALK translocations. For NGS, the Oncomine Solid Tumour Fusion Transcript Kit (Thermo Fisher Scientific, Waltham, MA) was used. The concordance was assessed using the Cohen κ coefficient (two-sided α ≤ 5%). Results: NGS provided results for 77 of the 95 cases tested (81.1%), whereas RT-PCR provided results for 77 of 96 (80.2%). Concordance occurred in 55 cases of the 60 cases tested with all four methods (43 ALK negative and 12 ALK positive). Using ALK copositivity for IHC and FISH as the criterion standard, we derived a sensitivity for RT-PCR/NGS of 70.0%/85.0%, with a specificity of 87.1%/79.0%. When either RT-PCR or NGS was combined with IHC, the sensitivity remained the same, whereas the specificity increased to 88.7% and 83.9% respectively. Conclusion: NGS evaluation with the Oncomine Solid Tumour Fusion transcript kit and RT-PCR proved to have high sensitivity and specificity, advocating their use in routine practice. For maximal sensitivity and specificity, ALK status should be assessed by using two techniques and a third one in discordant cases. We therefore propose a customizable testing algorithm. These findings significantly influence existing testing paradigms and have clear clinical and economic impact.